Pemidanaan Terhadap Pelaku Tindak Pidana Pengelolaan Limbah Bahan Berbahaya dan Beracun Tanpa Izin - Tarigan, Dear Padani (Universitas Kapuas, 2024)
A general case of hazardous and toxic waste pollution in Indonesia is the case of managing hazardous and toxic waste without a permit. Environmental Protection and Management Law Number 32 of 2009 has formulated minimum and maximum penalties, punishment for violations of quality standards, expansion of evidence, integrated criminal law enforcement, and regulation of corporate criminal acts. According to Environmental Protection and Management Law Number 32 of 2009 Environmental Protection and Management, hazardous and toxic waste management is an activity that includes reducing, storing, collecting, transporting, utilizing, processing and/or landfilling. The problem discussed in this research is how judges consider juridically, philosophically, sociologically and in the theory of retaliatory/absolute punishment regarding the punishment of perpetrators of the crime of managing hazardous and toxic waste without a permit so that the perpetrators are sentenced to a minimum imprisonment in the Salatiga District Court Conviction Number 115/Pid.B /LH/2019/PN.Slt. In this case, the author wants to find the law in the Salatiga District Court Conviction Number 115/Pid.B/LH to provide sentencing guidelines in giving minimums imprisonment for the same criminal incident. This type of research is normative juridical which is carried out based on legal materials and statutory regulations by examining theories, concepts and legal principles related to this research.